Ag2Cu2O3 – a catalyst template material for selective electroreduction of CO to C2+ products. Issue 9 (30th July 2020) - Martić, Nemanja; Reller, Christian; Macauley, Chandra; Löffler, Mario; Reichert, Andreas M.; Reichbauer, Thomas; Vetter, Kim-Marie; Schmid, Bernhard; McLaughlin, David; Leidinger, Paul; Reinisch, David; Vogl, Christoph; et al.
Abstract : Employing Ag2 Cu2 O3, a mixed metal oxide, as a template catalyst material for electrochemical reduction of CO enables generation of multi-carbon products with a faradaic efficiency of close to 92%, at a current density of 600 mA cm −2 . Abstract : Although recent years have brought significant progress within the field of electrochemical conversion of CO2 and CO to value-added chemicals, many more challenges need to be overcome for this technology to be implemented on an industrial level. Rational design of catalyst materials that would enable selective production of desired products at industrially relevant current densities (>200 mA cm −2 ) is most certainly one of them. Here, we introduce Ag2 Cu2 O3, a mixed-metal oxide, as a starting template material for efficient electroreduction of CO to C2+ products. By combining results from electrochemical real-time mass spectrometry (EC-RTMS), XRD and XPS we confirmed the template nature of Ag2 Cu2 O3 and in situ formation of a fully reduced CuAg bimetallic material during the first minutes of electrolysis. Electrochemical screening of the catalyst revealed significantly varying product distributions when CO2 (CO2 RR) and CO (CORR) where used as feed gases. During CORR, a faradaic efficiency close to 92% towards C2+ products at 600 mA cm −2 was achieved. On the other hand, during CO2 RR, CO was found to be the main product under all tested current densities, reaching a maximum faradaic efficiency of 68%. XPS valence band spectra of the bimetallic surface originating from Ag2 Cu2 O3 showed that its d-band electronic structure is noticeably different compared to metallic Ag and Cu, a finding we link to the observed product distributions. Finally, additional microscopy characterization techniques were used to investigate the observed surface reconstruction of the catalyst material under reaction conditions.